How to reach the land of Cockaigne? Edgeworth cycle theory and why a gasoline station is the first to raise its price - Mats Petter Kahl; Thomas Wein (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2022)
Competition in the German gasoline retail market is characterized by strong intraday price cycles. The cycles are described in the literature as corresponding to the well-known Edgeworth cycles. Cyclical pricing patterns are observable all over Germany and throughout the world. So far, research has focused on analyzing price patterns using average prices. We are the first to study the initiation of new price cycles by looking at the exact timing of competition in the daily cycle. We modified the data to be able to analyze local competition on a second-by-second level. What determines that a certain gasoline station increases its price to initiate a new price cycle? We are the first to empirically analyze whether the theoretically and economically significant price differences of the Edgeworth cycles explain the cyclical patterns throughout a day, or whether brand affiliation, local characteristics, or services offered predict the behavior of price increases. To provide first evidence and to do justice to the complexity of analyzing second-by-second intraday price cycles, we limit ourselves to one local market in Germany. We find that price considerations, as well as services offered, play a minor role in explaining why a gasoline station is the first to increase its price. Brand affiliation, as well as location parameters, are much more important in a gasoline stations' decision on whether they will be the first to increase prices. Furthermore, we show that the dominant suppliers Aral and Shell, who jointly account for more than 80 percent of price increases in the market, are the major drivers of the size of the price cycles. Together, the strong results for oligopoly players Aral and Shell suggest that market power is the major driver of the cyclical pricing pattern in the gasoline market.
Keywords: L13; L41; K21; 330; Edgeworth cycles; gasoline prices; dynamic pricing; gasoline market